Obowiązek „celibatu wstrzemięźliwości” duchownych w Kościele starożytnym według przepisów prawa kościelnego i prawa rzymskiego (IV - V wiek) - Wąsik, Wojciech Stanisław (Vox Patrum, 2024)
In the ancient Church, celibacy was not known in the sense of the obligation of higher clergy to maintain celibacy. Married men as well as voluntarily unmarried men were ordained. There was, however, a practice of complete continence by deacons, presbyters and bishops after they had been ordained. Until the 4th century, there were no norms of law established by the Church on this issue, which resulted from the strict provisions of Roman law, which was aimed at celibates. The point was not to give an excuse to persecute Christians. Only the introduction of new rules of religious policy by Constantine the Great in the 4th century changed the situation. The Synod of Elvira introduced the oldest, established particular law concerning celibacy of continence. Successive synods ordered the clergy to exercise continence due to their service performed to God, and for failing to do so [exercise continence], they were punished by losing their church office. The synod forbade ordaining men who were married a second time, and the so-called spiritual marriages of the clergy with syneisacts. The First Council of Nicaea introduced a law for the whole Church. It not only ordered clergymen to live in a perfect continence, but it also forbade married clergymen from living with their lawful wife. Popes from the 4th and 5th centuries issued decretals ordering the clergy to maintain celibacy of continence, and they justified this by the worship of God. Also Roman state law sanctioned the celibacy of continence existing in the Church.